2023
DOI: 10.3390/microorganisms11122953
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Cordycepin (CD) Inhibition for NRP1/CD304 Expression and Possibly SARS-CoV-2 Susceptibility Prevention on Cancers

Ting Li,
Na Luo,
Jiewen Fu
et al.

Abstract: NRP1/CD304 is a typical membrane-bound co-receptor for the vascular endothelial cell growth factor (VEGF), semaphorin family members, and viral SARS-CoV-2. Cordycepin (CD) is a natural product or active gradient from traditional Chinese medicine (TCM) from Cordyceps militaris Link and Ophiocordyceps sinensis (Berk.). However, NRP1 expression regulation via CD in cancers and the potential roles and mechanisms of SARS-CoV-2 infection are not clear. In this study, online databases were analyzed, Western blotting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…The VEGF level correlates with TGF-β levels. Recent reports have shown that NRP1, a cellular surface receptor for SARS-CoV-2 [ 10 ], can interact with ENG and VEGFR2 to regulate VEGF signaling and endothelial cell sprouting [ 11 ]. In addition, ENG may be affected by the BMP9-mediated pathway [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The VEGF level correlates with TGF-β levels. Recent reports have shown that NRP1, a cellular surface receptor for SARS-CoV-2 [ 10 ], can interact with ENG and VEGFR2 to regulate VEGF signaling and endothelial cell sprouting [ 11 ]. In addition, ENG may be affected by the BMP9-mediated pathway [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%